Novel 1,2,4-triazole-derived Schiff base derivatives: Design, synthesis, and multi-enzyme targeting potential for therapeutic applications - Ozcan, Ibrahim; Alici, Hakan; Taslimi, Parham; Tahtaci, Hakan; Taslimi, Parham (Academic Press Inc Elsevier Science, 2025)
This study synthesized a series of Schiff base derivatives featuring a 1,2,4-triazole framework and characterized through FT-IR, 1H NMR, 13C NMR, 19F NMR, MS, and elemental analysis. Subsequently, the inhibitory activities of these compounds were systematically evaluated in vitro against human carbonic anhydrase (hCA) isozymes I and II, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE). The results revealed that compounds 5a and 5c were particularly effective against cholinesterase enzymes, demonstrating their potential for neuroprotective applications. Meanwhile, compounds 5f and 5g exhibited remarkable inhibition of hCA I and II isozymes, suggesting their promise as selective inhibitors for therapeutic areas. Furthermore, molecular docking analyses revealed strong and specific interactions between the active compounds and enzyme binding sites, further supported by molecular dynamics simulations. Additionally, ADMET profiling of all compounds indicated favourable pharmacokinetic properties. The ADMET results suggest that these compounds hold significant potential for clinical applications in central nervous system and various disorders. These findings strongly suggest that the synthesized compounds are promising candidates for addressing unmet therapeutic needs in neurodegenerative and metabolic disorders, with potential applications in multienzyme targeting therapies.
Keywords: 4-Triazole; Schiff Bases; Enzyme Inhibition; Molecular Dynamic Simulations; Molecular Docking